Frequency of Vaginal Birth after C-Section and Factors Associated with Successful Trial of Vaginal Birth after C-Section : Vaginal Birth after C-Section Success and Factors - Janjua, Mahham; Syed, Sadaf Zahra; Javaid, Farkhanda; Mehmud, Quraa; Zafar, Iqra; Zafar, Abeera (Pakistan Journal of Health Sciences, 2025)
A repeat cesarean section is often a more favorable and comfortable option for women who have previously undergone a cesarean section. Objective: To determine the prevalence and the maternal and obstetric factors influencing the likelihood of a successful vaginal birth after cesarean (VBAC) among women attempting a trial of labor. Methods: This descriptive case series was conducted at the Gynecology Unit 3 of Sir Ganga Ram Hospital, Lahore, from August 2023 to February 2024. A total of 158 women with a history of one prior lower-segment cesarean section were enrolled through a non-probability sampling technique. Labor progression was monitored using the WHO labor guide, which guided the decision for either a repeat cesarean section or a vaginal birth. Data on factors associated with a successful VBAC were collected and analyzed by comparing their frequency between successful and unsuccessful cases. Results: Among the women undergoing a trial of labor, 115 (72.78%) achieved a successful vaginal delivery. When comparing maternal and obstetric factors between successful and unsuccessful groups, the following differences were observed: maternal age below 30 years (55.65% vs. 39.53%), gestational age under 40 weeks (59.13% vs. 48.84%), BMI less than 25 kg/m² (57.39% vs. 30.23%), and an inter-delivery interval exceeding two years (80.0% vs. 60.47%). Conclusions: This study found that the success rate of vaginal delivery in women with a prior cesarean section undergoing a trial of labor was 72.78%. Several maternal and obstetric factors were associated with an increased likelihood of successful VBAC.